COLLABORATIVE GOVERNANCE OF DISASTER MANAGEMENT TOWARD LOCAL RESILIENCE: THE CASE OF RESEARCH ON LUMAJANG REGENCY, INDONESIA (Lex localis - Journal of Local Self-Government, 2025)
This study aims to investigate the dynamics of collaborative governance in disaster management and its contribution to enhancing local resilience, with a specific focus on Lumajang Regency, Indonesia. A qualitative method was adopted to analyze the interactions, coordination, and shared responsibilities among diverse stakeholders, including local government agencies, community-based organizations, the private sector, and civil society, in responses to and recovery from disasters, particularly volcanic eruptions and floods that recurrently affected the region. Data were gathered through in-depth interviews, focus group discussions, and document analysis with key stakeholders in Lumajang’s disaster management ecosystem. The results showed that shared leadership, mutual trust, institutional capability, and community participation contributed to the implementation of collaborative governance in Lumajang Regency. This study also identified major challenges, such as poor coordination, inequitable resource distribution, and inconsistent policy implementation. Despite these issues, Lumajang demonstrated resilience through adaptive learning, inclusive engagement, and the strengthening of inter-organizational networks. Furthermore, the analysis indicated that enhancing collaborative governance structures was crucial for improving disaster preparedness, response, and recovery at the local level. The results provided valuable insights for policymakers and practitioners sourcing to improve disaster resilience through multi-actor engagement in Indonesia and other similarly disaster-prone regions.